Does Thrombolysis Have a Place in the Cardiopulmonary Resuscitation of Patients With Acute Pulmonary Embolism? A Case of Successful Thrombolysis During Pulmonary Embolism Induced Cardiopulmonary Arrest. Issue 5 (May 2016) - Namiranian, Khodadad; Rathi, Nisha K.; Banchs, Jose; Price, Kristen J.; Nates, Joseph L.; Haque, Sajid A.
Abstract : Objective: Pulmonary embolism often causes cardiac arrest. When this occurs, thrombolytic therapy is not routinely administered. There are multiple reasons for this, including difficulty with rapidly adequately diagnosing the embolus, the lack of good data supporting the use of thrombolytics during resuscitation, the belief that thrombolytic therapy is ineffective once a patient has already arrested, the difficulty of obtaining thrombolytics at the bedside rapidly enough to administer during a code, and the increased risks of bleeding, particularly with ongoing chest compressions. In this case report, we present a patient who was successfully treated with thrombolytic therapy during pulmonary embolism–induced cardiopulmonary arrest and discuss the role of thrombolytics in cardiopulmonary resuscitation. Design: Case report. Setting: Surgical ICU in a comprehensive cancer center. Patient: A 56-year-old man who developed hypotension, dyspnea, hypoxia, and pulseless electrical activity 10 days after resection of a benign colon lesion with a right hemicolectomy and primary end-to-end anastomosis. Interventions: After a rapid bedside echocardiogram suggesting pulmonary embolus, thrombolytic therapy was administered during cardiopulmonary resuscitative efforts. Measurements and Main Results: The patient had a return of spontaneous circulation and showed improvement in repeat echocardiographic imaging. He had a prolonged course in the ICU and hospital, but eventually made an essentially complete clinical recovery. Conclusion: As bedside echocardiographic technology becomes more rapidly and readily available, the rapid diagnosis of pulmonary embolism and use of thrombolytics during cardiopulmonary resuscitation may need to be more routinely considered a potential therapeutic adjunctive measure.